Effectiveness of Green Waqf in Supporting Local Climate Projects: Governance and Sustainability Analysis In West Java - Sahrotul Jannah; Agil Hidayatullah; Navilah Ulliyah (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2026)
Background: Climate change and environmental degradation, intensified by rapid urbanization and industrialization in West Java, underscore the urgent need for innovative Islamic social finance instruments to support sustainable local development and climate action. Objectives: This study aims to assess how the effectiveness, governance, institutional design, and resource allocation of green waqf initiatives support local climate action, environmental sustainability, and community welfare in West Java Province. Novelty: This study empirically integrates Data Envelopment Analysis (DEA) with institutional governance evaluation to link governance quality and green waqf efficiency, demonstrating the contribution of Islamic social finance to SDGs 6, 7, 13, and 15. Research Methodology / Design: This study applies a mixed-method approach, integrating Data Envelopment Analysis (DEA) to assess the efficiency of five green waqf projects based on financial, human, and asset inputs with their social and environmental outputs, and content analysis of institutional and policy documents to examine governance quality, transparency, and community participation. Findings: The study shows that green waqf projects with strong governance, transparency, and community participation achieve higher efficiency and sustainability through better institutional capacity and multi-stakeholder collaboration. Implication: These findings contribute to the development of Islamic social finance by strengthening the theoretical understanding of the link between efficiency and governance in green waqf management and providing practical recommendations for BWI, the Ministry of Religious Affairs, and the West Java Provincial Government to enhance governance frameworks and integrate sustainability indicators in future evaluations.